The Clinical Significance of Changes in the Expression Levels of MicroRNA-1 and Inflammatory Factors in the Peripheral Blood of Children with Acute-Stage Asthma. (26th June 2018) - Tian, Man; Zhou, Ying; Jia, Haoyuan; Zhu, Xuming; Cui, Yubao
Abstract : This study assessed the changes and clinical significance of microRNA-1 (miR-1) and inflammatory factors in the peripheral blood of children with acute-stage asthma. 100 children with acute-stage asthma (study group) and 100 healthy children (control group) were enrolled. For all enrolled children, the peripheral blood levels of miR-1, interleukin-4 (IL-4), IL-5, IL-8, tumor necrosis factor-alpha (TNF- α ), and interferon- γ (IFN- γ ) were measured. The relative expression levels of miR-1 and IFN- γ in the peripheral blood of children in the study group were significantly lower than those in the control group, whereas expression levels of IL-4, IL-5, IL-8, and TNF- α were significantly higher. Moreover, these levels changed to a greater extent in patients with severe disease ( P < 0.05). Further analyses showed that the miR-1 expression level positively correlated with IFN- γ and negatively correlated with IL-4, IL-5, IL-8, and TNF- α expression levels ( P < 0.05). ROC curve analysis to identify diagnostic specificity and sensitivity showed that, for diagnosing exacerbation in asthma, the area under the curve (AUC) for miR-1 was the highest (AUC = 0.900, P < 0.05) of all tested markers; this held true for diagnosing severe asthma as well (AUC = 0.977, P < 0.05). Compared to healthy children, children with acute-stage asthma had a low miR-1 expression level and a Th1/Th2 imbalance in their peripheral blood. The changes were closely related, became more exaggerated with an increase in disease severity, and could be used as auxiliary variables for diagnosing asthma exacerbation and evaluating disease severity.